2018
DOI: 10.1007/s00426-018-0974-y
|View full text |Cite
|
Sign up to set email alerts
|

Count on arousal: introducing a new method for investigating the effects of emotional valence and arousal on visual search performance

Abstract: There is a large body of research, indicating that threatening stimuli with evolutionary history are prioritised in visual processing. It has been proposed that all threatening stimuli are prioritised, irrespective of evolutionary age, but it was argued that the method used to produce the results was not suitable for investigating the phenomenon. We present a new visual search task and provide evidence that it is an appropriate tool for future research. In Experiment 1, we investigated how the influence of emo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
39
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 50 publications
8
39
0
1
Order By: Relevance
“…According to the arousal stimulation effect (Zsido, Bernath, Labadi, & Deak, 2018), although threatening stimuli initially grab the attention leading to reduced performance compared to neutral stimuli, increase in the level of arousal could compensate for the negative effects caused by cognitive resources devoted to task-irrelevant information. That is, a heightened arousal or threat level would result in a speeded reallocation of these resources to the task from the irrelevant distractor while at the same time increasing the availability of cognitive resources by stimulating the cognitive system (see also Meyer, Quaedflieg, Bisby, & Smeets, 2019;€ Ohman, Esteves, Flykt, & Soares, 1993;Reisenzein, 1994;Sakaki, Niki, & Mather, 2012;Trick, Brandigampola, & Enns, 2012;Zinchenko, Geyer, M€ uller, & Conci, 2019).…”
Section: The Arousing Effect Of Threatening Stimulimentioning
confidence: 99%
See 2 more Smart Citations
“…According to the arousal stimulation effect (Zsido, Bernath, Labadi, & Deak, 2018), although threatening stimuli initially grab the attention leading to reduced performance compared to neutral stimuli, increase in the level of arousal could compensate for the negative effects caused by cognitive resources devoted to task-irrelevant information. That is, a heightened arousal or threat level would result in a speeded reallocation of these resources to the task from the irrelevant distractor while at the same time increasing the availability of cognitive resources by stimulating the cognitive system (see also Meyer, Quaedflieg, Bisby, & Smeets, 2019;€ Ohman, Esteves, Flykt, & Soares, 1993;Reisenzein, 1994;Sakaki, Niki, & Mather, 2012;Trick, Brandigampola, & Enns, 2012;Zinchenko, Geyer, M€ uller, & Conci, 2019).…”
Section: The Arousing Effect Of Threatening Stimulimentioning
confidence: 99%
“…We adopted a visual number finding task from a previous study (Zsido, Bernath, Labadi, & Deak, 2018) where threatening or neutral images were presented as background pictures and different number matrices as foreground. Participants had to find the numbers in ascending order, and their performance was measured, that is the last number they found during a given time.…”
Section: Present Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The affective content can affect observers’ emotional and arousal states, and subsequently bias their attention to such stimuli rather than recruit attentional resources per se . In line with this, it has been shown that images with negative valence affects visual-search performance (e.g., [ 37 ]). Similarly, there is evidence that images with different affective content (e.g., positive versus negative valence images) affect perceived pain intensity of different types of noxious stimulation (e.g., [ 2 3 , 38 39 ]; for a review see [ 13 ]).…”
Section: Introductionmentioning
confidence: 64%
“…Extensive literature has examined the link between affective information and cognition and has shown how affective stimuli can directly modulate cognitive performance through bottom-up processes such as attention orientating, and consequently memory ( Murphy and Isaacowitz, 2008 ; Talmi et al, 2008 ; Brenner et al, 2014 ; Padulo et al, 2020 ). More specifically, the boost in sensory processing for emotionally salient events ( Vuilleumier, 2002 , 2005 ), enhances attention toward them and/or alters attention toward other concomitant stimuli ( Dennis and Chen, 2007 ; Bocanegra and Zeelenberg, 2009 ; Vuilleumier and Huang, 2009 ) and ultimately leads to more efficient encoding and consolidation in memory.…”
Section: Introductionmentioning
confidence: 99%